Tradition, heredity and genetic for region´s productivity - Rincón Trujillo, Helka Liliana
This article presents the pedagogical practice of instructor Eywar Niño, a perfect example of the kind of professional the institution is willing to reproduce in every centre around the country. The countryside is his natural predilection, ovine breeding and the capability of teaching, he had the wisdom of using all of those resources as the raw material for his professional training. Because of that, he is a coherent professional with the way he senses and lives life, he shares his knowledge and experience, he strongly believes in the ovine race improvement as the most profitable path for producers and surely, he seeks the perfection in himself as the apprentice and instructor, the best way to work his land, the one recognized as the cattle industry in Colombia.